Ginsenoside Rg1 treatment alleviates renal fibrosis by inhibiting the NOX4–MAPK pathway in T2DM mice. Issue 1 (31st December 2023) - Ji, Pengmin; Shi, Qifeng; Liu, Yan; Han, Min; Su, Yong; Sun, Ran; Zhou, Huimin; Li, Weizu; Li, Weiping
Abstract: Diabetic kidney disease (DKD) is a severe complication of type 2 diabetes mellitus (T2DM). However, the pathogenesis of DKD remains unclear, and effective treatment strategies are still lacking. Ginsenoside Rg1 (Rg1) has been reported to improve DKD, but the mechanism is unclear. NADPH oxidase 4 (NOX4) is an essential reactive oxygen species (ROS) source in the kidney. The mitogen-activated protein kinase (MAPK) signaling may exacerbate renal fibrosis. Therefore, we hypothesized that Rg1 might alleviate renal injury and fibrosis by inhibiting NOX4 and MAPK signaling in T2DM-induced DKD. We found that Rg1 significantly improves lipid deposition, fibrosis, and ROS production and reduces NOX4, p22phox, p47phox, p-ERK, p-JNK, and p-P38 MAPK expressions in the T2DM mice kidneys. We also found that the high-fat diet treatment in mice and the palmitate (PA) and PA + HG (high glucose) exposure in human mesangial cells could significantly induce lipid deposition, ROS production, fibrosis, and the activation of NOX4–MAPK signaling. The results suggest that high lipid and glucose may play a significant role in DKD progression, while Rg1 may attenuate renal fibrosis by inhibiting NOX4–MAPK signaling.